(untitled) (Research, Society and Development, 2025)
The present study aimed to develop and evaluate a simple, low-cost, and rapid qualitative method for the preliminary screening of methanol in distilled alcoholic beverages, based on the induction of alkaline separation mediated by a dye. The procedure consisted of adding solid sodium hydroxide and a gel food dye to commercial beverages and reference solutions, followed by manual agitation and brief resting, allowing visual distinction between samples free of methanol—which formed two well-defined phases—and adulterated samples above a critical threshold, which exhibited a single homogeneous phase. Several categories of distilled spirits were analyzed, as well as solutions prepared with decreasing concentrations of methanol. The results demonstrated high reproducibility for both positive and negative samples, while revealing a transition zone between 1.5% and 4% (v/v) in which miscibility exhibited variable behavior. Concentrations equal to or greater than 5% produced unequivocally positive results. All commercial beverages tested were free of methanol within the sensitivity of the method. It is concluded that the proposed technique is suitable as a preliminary screening tool, with sensitivity compatible with methanol concentrations typically found in adulterated beverages associated with poisoning outbreaks, thus offering a valuable resource for inspection activities, forensic investigations, and public health prevention efforts.